2020
DOI: 10.1017/s1355617720000697
|View full text |Cite
|
Sign up to set email alerts
|

The Art of Remediating Age-Related Cognitive Decline: Art Therapy Enhances Cognition and Increases Cortical Thickness in Mild Cognitive Impairment

Abstract: Objective: Previous research on art therapy (AT) in cognitive aging has been lacking. AT can potentially engender significant cognitive gains, due to its rigorous cognitive involvement, making it useful to tackle age-related cognitive decline. Along with these cognitive gains, associated neuroplastic changes are hypothesized to arise from AT as well. The current intervention examined the effects of an AT intervention on cognitive outcomes and cortical thickness (CT) among participants with mild cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
7
0
4
Order By: Relevance
“…To date, mild cognitive impairment is drawing much attention to the importance of painting intervening at this stage in order to alter the course of subsequent cognitive decline as soon as possible (Petersen et al, 2014). Recently, a randomized controlled trial (Yu et al, 2021) showed significant relationship between improvement immediate memory/working memory span and increased cortical thickness in right middle frontal gyrus in the painting art group. With the long-term cognitive stimulation and engagement from multiple sessions of painting therapy, it is likely that painting therapy could lead to enhanced cognitive functioning for these patients.…”
Section: Depression Disorders and Anxietymentioning
confidence: 99%
“…To date, mild cognitive impairment is drawing much attention to the importance of painting intervening at this stage in order to alter the course of subsequent cognitive decline as soon as possible (Petersen et al, 2014). Recently, a randomized controlled trial (Yu et al, 2021) showed significant relationship between improvement immediate memory/working memory span and increased cortical thickness in right middle frontal gyrus in the painting art group. With the long-term cognitive stimulation and engagement from multiple sessions of painting therapy, it is likely that painting therapy could lead to enhanced cognitive functioning for these patients.…”
Section: Depression Disorders and Anxietymentioning
confidence: 99%
“…Whether and to what extent art-based therapy can protect against age-related cognitive decline or dementia is not yet clear as studies had only small sample sizes and low quality of study findings [ 50 ]. A recent study from Yu et al [ 51 ] points out that art-based therapy can strengthen and enhance certain cognitive functions, such as immediate memory and working memory span, and increase in cortical thickness in the middle frontal gyrus [ 51 ]. Based on our findings, we believe that people with dementia might benefit from non-verbal creative activities in an ill-defined problem space, in which they can chose a logic or association freely rather than following strict rules.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been found that art-based therapies and interventions can effectively be used to reduce pain, stress, depression, breathlessness and other symptoms in patients with several medical conditions [ 31 ]. Last, but not least, despite us not assessing cognitive functions, the scientific literature reports the possible use of art therapy to improve these domains [ 34 ], also reporting that some diseases may improve the personal disposition of neurological patients to produce art [ 35 ]. Further studies are needed to deeply investigate these aspects that were not evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%